Association of body mass index with peer aggression, reaction to peer aggression and physical activity in rural Chinese children - Tao, Sixiang; Wang, Hongzhao; Song, Yaming; Koh, Denise (Frontiers in Public Health, 2025)
ObjectivesTo investigate the relationship between body mass index (BMI) and peer aggression, reaction to peer aggression, and physical activity in rural Chinese children.Materials and methodsThe Chinese version of the Peer Aggression and Reactive Behavior Questionnaire assessed children's peer aggression and reaction to peer aggression; the Chinese version of the Physical Activity Questionnaire for Children assessed physical activity in the last week. Study was conducted in four rural junior high schools in Fuyang City, Anhui Province, and 356 first-grade students were finally included. Participants were classified into six categories (from −2SD to +3SD) according to the WHO BMI criteria for children. The Kruskal–Wallis H-test and Mann–Whitney U-test were used for between-group comparisons. Spearman correlation analyses and restricted cubic spline analyses were used to assess the relationships between BMI and behavioral indicators. All data analyses were done using R Studio.ResultsBMI was significantly and non-linearly associated with peer aggression, which increased significantly after BMI exceeded +1SD (+2SD: r = 0.366, p < 0.01; +3SD: r = 0.807, p < 0.001). Physical activity tended to decrease with increasing BMI and was significantly negatively correlated with peer aggression in the high BMI group (r = −0.972, p < 0.001). Reaction to peer aggression increased with BMI, but the association was insignificant.ConclusionsBMI in rural children was significantly associated with peer aggression and physical activity, and physical activity may play a moderating role between BMI and aggression. This finding provides new ideas for the intervention of aggression in rural children and highlights the importance of integrating weight management, physical activity, and behavioral interventions.